CAMPUR KODE PADA MASYARAKAT ETNIK JAWA-SUNDA: KAMAN SOSIOLINGUISTIK DALAM RANAH PEMERINTAHAN DI KABUPATEN BREBES - Tommy Yuniawan (Humaniora, 2005)
This study is aimed to describe code mixing in Sundanese-Javanese society in the domain of governmental affairs at Brebes regency. The study data are in the from of conservations or speech parts in the domain of governmental affairs at Brebes . Regions to be the focus of observation are Kubangpari representing urban areas & Baros representing rural areas. the data are colected by using observation & interiew method which employs listening technique . Afterward, the data are analyzed by means of 2 procedure, (I) analysis during data collection included & (2) analysis after data collection . In order to achieve accurate interpretation result, the writer flows these steps : (1) discussion, (2) rechecking, and (3) consultation . The conclusion is that the realization of code mixing in Javanese-Sundanese society in the domain of govermental affairs, at Brebes consist of : I) Brebes-Javanese language code mixing in Indonesian, (2) Brebes- Javanese language code-mixing in Indonesian, (3) Brebes-Javanese language code mixing in Brebes-Javanese language, (4) Brebes-Javanese language code mixing in Indonesian, (5) Ngoko-Javanese language code mixing in Indonesian, and (6) Krama Javanese language code-mixing in Indonesian. The result of the study may be helpful for further research in the fields of language development and organization of both regional language and Indonesian .